2019
DOI: 10.17269/s41997-019-00189-1
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Inuit health through a participatory whiteboard video

Abstract: Setting The Inuit community of Rigolet experiences greater rates of self-reported acute gastrointestinal illness (AGI) compared to southern Canada. Intervention A whiteboard video tool was collaboratively developed by Rigolet youth, community members, the research team and key regional stakeholders to share public health recommendations for reducing the risk of AGI. The video debuted in Rigolet at a community event in August 2016 and was later provided online for community members and local and regional health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 27 publications
0
57
0
1
Order By: Relevance
“…Essentially, a great deal of academic research has furthered the colonial agenda rather than questioned or denounced it. However, Indigenous communities throughout Canada and around the world are transforming health research in ways that respond to community priorities, contribute to Indigenous self-determination, and insist on research that is led and governed by Indigenous Peoples [8][9][10][11][12]. This is the essence of community-driven Indigenous health research [13].…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, a great deal of academic research has furthered the colonial agenda rather than questioned or denounced it. However, Indigenous communities throughout Canada and around the world are transforming health research in ways that respond to community priorities, contribute to Indigenous self-determination, and insist on research that is led and governed by Indigenous Peoples [8][9][10][11][12]. This is the essence of community-driven Indigenous health research [13].…”
Section: Introductionmentioning
confidence: 99%
“…The age range of youth involved in included studies ranged between 11 to 24 years. All studies utilized fun and interactive strategies to engage youth in their respective studies with the outcomes aimed at promoting health, developing capacity in youth participants and engaging youth in collaborating on sustainable outcomes for and with their communities [ 5 , 8 , 40 , 44 , 57 , 71 – 84 ], save for one [ 16 ]. The summary of individual sources of evidence is described in Table 5 .…”
Section: Discussionmentioning
confidence: 99%
“…They expressed a feeling of self-awareness and the capacity to thrive in their communities. Authors identified that the lack of action following the interactive performances was a limitation and direction for further research inquiry 19 Saini et al, 2020 [ 84 ]. To share public health information about acute gastrointestinal illness (AGI) by co-developing a whiteboard video with Inuit youth, community members and government partners and evaluating its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Sebelumnya, penggunaan metode alternatif yang melibatkan komponen audio-visual dikenal terbatas pada penelitian-penelitian berbasis seni (Creswell & Poth, 2016); namun saat ini metode audio-visual telah berkembang dalam kelompok ilmu selain seni, seperti ilmu sosial (Friend & Militello, 2015;Pink, 2006). Para sarjana dari berbagai disiplin ilmu telah menunjukkan kekuatan integrasi teknik media audio-visual dalam proses penelitian sosial, seperti antropologi visual (Ruby, 2005), sinema etnografis (Ariefiansyah & Prahara, 2013;Durington & Ruby, 2011;MacDonald, 2013), design thinking (Katoppo & Sudradjat, 2015), praktik PhotoVoice (Liebenberg, 2018), podcasting (Jati, 2021;Rogers et al, 2020), dan praktik video whiteboard (Saini et al, 2020). Dalam bidang pendidikan sejarah, hasil akhir penelitian dalam bentuk film dokumenter merupakan upaya akademisi jurusan sejarah dalam mengeksplorasi media baru untuk menunjukan cerminan kebenaran atau fakta (Ratmanto, 2018).…”
Section: Pendahuluanunclassified